Can fiscal transfers effectively reduce poverty in the Gorontalo Province? - Arham, Muhammad Amir; Humalanggi, Mahyudin; Tantawi, Rezkiawan; Kusuma, Citra Aditya (Program Magister Ilmu Ekonomi Pascasarjana Universitas Jambi, 2024)
The central government has increasingly diversified and expanded fiscal transfers to local authorities to enhance community welfare rapidly. However, in Gorontalo, although poverty rates have declined, the pace of reduction has slowed despite an increase in the value of transfers. This study aims to identify the fiscal transfer mechanisms most effective in reducing Gorontalo's poverty rate. It focuses on several types of fiscal transfers, including the Special Allocation Fund (DAK), Village Fund Allocation (ADD), Family Hope Program (Program Keluarga Harapan, PKH), Smart Indonesia Program (Program Indonesis Pintar, PIP), and Social Assistance. Utilizing panel data regression analysis covering all six districts/cities in Gorontalo Province over the last five years (2018-2022) and employing the Fixed Effects Model (FEM), the findings suggest that PIP assistance has the most significant impact on poverty reduction, although its effects are more long-term. Moreover, the study finds that while ADD transfers notably enhance community welfare, the two-decade-long DAK transfers have inadvertently worsened poverty levels in Gorontalo. This issue stems from the DAK's allocation formula, which does not directly target the income improvement of low-income populations. Both PKH and Social Assistance have shown little positive effect on poverty alleviation in the region. Consequently, the study recommends that the government prioritize expanding and funding enhancement of PIP assistance, considering many underprivileged individuals remain unreached by this support. Additionally, it suggests increasing the ADD to accelerate development in poverty-stricken rural areas.